(untitled) (Scientia Agricola, 2005)
To evaluate the behavior of micropropagated heliconia seedlings during the acclimatization process using different substrates and shade levels, seedlings of H. bihai (Lobster Claw I) were planted in plastic trays using the substrates: washed sand, vermiculite (medium texture), and PlantMax® Horticultura, and shade cloths with percentages of 0% (full sun), 30%, 40%, 50%, 60%, 70%, and 80% of shade in relation to full sun. Best results were obtained for washed sand and PlantMax substrates at shade conditions starting from 50%, especially at 70% and 80%. Pre-existing roots from in vitro rootings were not functional, not presenting secondary roots, and showing root tissue necrosis. Acclimatized seedlings developed new roots. This finding suggests that this plant can be acclimatized without going through a laboratory rooting stage.